Affirmative action and racial preference : a debate - Cohen, Carl, 1931- (Point/counterpoint series (Oxford, England), 2003)
Cohen and Sterba, two contemporary philosophers in sharp opposition, debate the value of affirmative action and racial preference. They defend thier views with analysis and commentay on landmark cases - including the decisions of the United States Supreme Court and the University of Michigan admissions cases, Gratz and Grutter.